Satisfaction with the academic specialization and its relationship to motivation for achievement among university students : Field study at the University of Tassoust Jijel - SIFFOUR, Salim (Journal of Human Sciences, 2020)
This study aimed to find out the relationship between satisfaction with the academic specialization and the motivation of achievement among university students. After applying these two scales to a sample of 50 students from the Faculty of Humanities and Social Sciences, the following results were reached is:- There is a statistically significant relationship between the satisfaction of the university specialization and the motivation of achievement among university students. - Satisfaction with university specialization is high among university students. - The level of motivation for achievement is high among university students.